2008
DOI: 10.1681/asn.2007121375
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Rapamycin in Anti-GBM Glomerulonephritis

Abstract: The immunosuppressive mammalian target of rapamycin inhibitor rapamycin is widely used in solidorgan transplantation, but the effect of rapamycin on kidney disease is controversial. This study evaluated the effect of rapamycin in the autologous phase of anti-glomerular basement membrane (anti-GBM) glomerulonephritis. Disease was induced by preimmunizing the animals with rabbit IgG 5 d before administration of rabbit anti-mouse GBM antiserum. When rapamycin was started on the day of immunization (group 1), mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 32 publications
3
30
2
1
Order By: Relevance
“…50,51 However, to our knowledge, there has been only one report on the role of mTOR activation in anti-GBM nephritis showing that pretreatment of rapamycin protected glomerular injury through affecting T-and B-cell activation. 52 However, the typical glomerular change in their animal model was severe mesangial expansion and not CGN. Role of LAT2 and mTORC1 in crescentic formation R Kurayama et al A major finding in the present study is that activation of mTORC1 pathway commenced in the glomerular PECs and podocytes before apparent crescent formation and increased in the crescent lesion itself of CGN (Figure 3a).…”
Section: Discussionmentioning
confidence: 97%
“…50,51 However, to our knowledge, there has been only one report on the role of mTOR activation in anti-GBM nephritis showing that pretreatment of rapamycin protected glomerular injury through affecting T-and B-cell activation. 52 However, the typical glomerular change in their animal model was severe mesangial expansion and not CGN. Role of LAT2 and mTORC1 in crescentic formation R Kurayama et al A major finding in the present study is that activation of mTORC1 pathway commenced in the glomerular PECs and podocytes before apparent crescent formation and increased in the crescent lesion itself of CGN (Figure 3a).…”
Section: Discussionmentioning
confidence: 97%
“…On the one hand, immune initiation and regulation takes place in the draining lymph nodes, and on the other hand, the immune effector phase is located in the kidneys. Based on previous observations of our group, we suggested that mainly the immune regulation taking place in the secondary lymphoid organs 14,16,24 can protect mice from NTS, whereas immune regulations in the kidney may only affect the severity of the disease. Here, we only detected significantly increased Tim3 expression in kidneys of mice subjected to NTS, whereas no significant increase was found in the draining lymph nodes.…”
Section: Tim3 and Nephrotoxic Serum Nephritis 1721mentioning
confidence: 84%
“…Because the B cell response is of relevance in our model of NTS, 24 we tested for putative differences of mouse-antirabbit IgG titers as a function of anti-Tim3 treatment. Seven days after induction of NTS, no difference in the whole immunoglobulin and immunoglobulin subclasses IgG1 and IgG3 concentrations were found in mice treated with either a Tim3-blocking antibody or the respective isotype control (Table 2).…”
Section: Effects Of Tim3 Blockade On Local B and T Cell Responses In Ntsmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental studies it was proposed that a decrease of vascular endothelial growth factor and/or an increase in proinflammatory cytokines such as interleukin-6 might be responsible for the pathologies observed. [6][7][8] Rapamycininduced proteinuria is not only observed in renal transplant patients, but was recently shown also in long-term cardiac transplant patients. 9 In patients after SCT data on the clinical efficacy of rapamycin is scarce.…”
mentioning
confidence: 93%